HBV reactivation in allogeneic stem cell transplant recipients: Risk factors, outcome, and role of hepatitis B virus mutations. Issue 10 (6th November 2017) - Anastasiou, Olympia E.; Almpani, Foteini; Herrmann, Anke; Gerken, Guido; Ditschkowski, Markus; Ciesek, Sandra
Abstract : Hepatitis B virus (HBV) reactivation (HBVr) in recipients of allogeneic hematopoetic stem cells (aHSCs) appears heterogeneously with respect to its frequency, manifestation, and outcome. The aim of this study was to present data from a large German cohort of recipients of aHSC transplantation (aHSCT), focusing on the incidence of HBVr in antibody to hepatitis B core antigen (anti‐HBc)‐positive aHSCT recipients, its clinical outcome, and the role of mutations in HBV. Between 2005 and 2015, 1, 871 patients received aHSCT at University Hospital Essen. A follow‐up of at least 6 months after transplant was available in 55 patients who were anti‐HBc‐positive; clinical and virologic data were analyzed. The HBV genome was sequenced with next generation technology from serum samples of 8 patients with HBVr. Thirteen out of 55 (23.6%) patients developed HBVr at a median of 26 months after aHSCT. After initiation of antiviral treatment, complete HBV DNA suppression was achieved in 7/10 (70%) patients 1 to 40 months after HBVr. Nine of 13 patients had increased alanine aminotransferase; 3 patients had compromised coagulation and model for end‐stage liver disease scores of 18‐27, and 1 of these patients died due to liver failure 5 weeks after HBVr. As a risk factor for HBVr, we identified anti‐HBc signal to cut‐off ration (S/CO) ≥7.5 before transplantation. Complete HBV DNA suppression was achieved in 7/10 patients; therapy‐relevant mutations were found in 1 patient. In 4/8 patients, immune escape mutations were detected either as majority or minority variants. Conclusion : HBVr is common in anti‐HBc‐positive aHRCT recipients and can lead to severe hepatitis with compromised coagulation. The level of anti‐HBc S/CO before transplantation is a risk factor for HBVr. Complete virologic response under adequate antiviral treatment could not be achieved in all patients. ( Hepatology Communications 2017;1:1014–1023)